2022
DOI: 10.1186/s12888-022-04464-3
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a workplace suicide prevention program in the Australian manufacturing industry: protocol for a cluster-randomised trial of MATES in manufacturing

Abstract: Males are at higher risk of death by suicide than females in Australia, and among men, blue-collar males are at higher risk compared to other working males. In response, MATES in Construction developed a workplace suicide prevention program for the construction sector in 2007 that has been widely implemented in Australia. In the current project, this program is being adapted and trialled in the manufacturing sector. The common aims of MATES programs are to improve suicide prevention literacy, help-seeking inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Poor research design coupled with variance in sample size across included studies further undermined the findings, with only four RCTs included in the review. While it is promising to see the recent registration of RCTs (LaMontagne et al, 2022), more are needed to build the evidence base to further the field.…”
Section: Discussionmentioning
confidence: 99%
“…Poor research design coupled with variance in sample size across included studies further undermined the findings, with only four RCTs included in the review. While it is promising to see the recent registration of RCTs (LaMontagne et al, 2022), more are needed to build the evidence base to further the field.…”
Section: Discussionmentioning
confidence: 99%
“…MATES is noteworthy due to the program’s successful diffusion amongst construction workers leading to wide dissemination in target areas ( Rogers, 2002 ; Oliffe et al , 2020 ). MATES uses an ‘Outrage, Hope, Action’ Model ( LaMontagne and Shann, 2020 ) to engage and motivate workers. The core objective of MATES is to increase awareness and engage workers collectively in suicide prevention ( Martin and Gullestrup, 2014 ; Neis and Neil, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MATES program logic model describes how program outputs are expected to generate program outcomes ( Table 1 ) including improved mental health and reduced suicidality ( LaMontagne and Shann, 2020 ). MATES is a program rolled out organically and continuously over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified that R. Brimelow and C. Lockwood were incorrectly assigned to affiliation 2. The authors are assigned to affiliation 3.…”
mentioning
confidence: 99%